Experimental study of bioethanol production using mixed cassava and durian seed - Seer, Q.; Nandong, Jobrun; Shanon, T. (IOP Publishing, 2017)
© Published under licence by IOP Publishing Ltd. The production of biofuels using conventional fermentation feedstocks, such as sugar-and starch-based agricultural crops will in the long-term lead to a serious competition with human-animal food consumption. To avoid this competition, it is important to explore various alternative feedstocks especially those from inedible waste materials. Potentially, fruit wastes such as damaged fruits, peels and seeds represent alternative cheap feedstocks for biofuel production. In this work, an experimental study was conducted on ethanol production using mixed cassava and durian seeds through fermentation by Saccharomyces cerevisiae yeast. The effects of pH, temperature and ratio of hydrolyzed cassava to durian seeds on the ethanol yield, substrate consumption and product formation rates were analyzed in the study. In flask-scale fermentation using the mixed cassava-durian seeds, it was found that the highest ethanol yield of 45.9 and a final ethanol concentration of 24.92 g/L were achieved at pH 5.0, temperature 35°C and 50:50 volume ratio of hydrolyzed cassava to durian seeds for a batch period of 48 hours. Additionally, the ethanol, glucose and biomass concentration profiles in a lab-scale bioreactor were examined for the fermentation using the proposed materials under the flask-scale optimum conditions. The ethanol yield of 35.7 and a final ethanol concentration of 14.61 g/L were obtained over a period of 46 hours where the glucose was almost fully consumed. It is worth noting that both pH and temperature have significant impacts on the fermentation process using the mixed cassava-durian seeds.